Human Capital Flight: The Cause of Underdevelopment - Wagle, Achyut (NRB Economic Review, 2008)
Since the beginning of development discourse based on dualism of development versus underdevelopment, particularly since the end of World War II, a large number of explanations and theorized school of thoughts have come to fore. Despite so many theories and models about development in place, so much technological and scientific advancement mainly in communication and transportation, the extent of underdevelopment is more rampant than ever before. The income of the richest 1 percent (50 million) is the same as the income of the poorest 60 percent (2.7 billion people) of the world. More than half of world population survives by less than US 2 a day. Apparently, these development theories have practically failed to address the problem of underdevelopment of the world. This reality–both in development discourse and development practice—make it imperative to rethink, mainly to specifically point out the causes of seemingly inescapable trap of poverty and underdevelopment. The recognition of the human capital flight as the most crucial cause of underdevelopment provides new basis for development discourse. On the contrary, Nepal has remained as one of the highly underdeveloped countries, the reason of which could be attributed to human capital flight.